Quarkonium phenomenology from a generalised Gauss law - Lafferty, David; Rothkopf, Alexander (Universe, 2019)
We present an improved analytic parametrisation of the complex in-medium heavy quark potential derived rigorously from the generalised Gauss law. To this end we combine in a self-consistent manner a non-perturbative vacuum potential with a weak-coupling description of the QCD medium. The resulting Gauss-law parametrisation is able to reproduce full lattice QCD data by using only a single temperature dependent parameter, the Debye mass m D . Using this parametrisation we model the in-medium potential at finite baryo-chemical potential, which allows us to estimate the Ψ ′ / J / Ψ ratio in heavy-ion collisions at different beam energies.
Gesehen am 22.10.2019